LARANGAN MEMBAWAKAN LAGU TANPA IZIN BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Marchellia, Sheila Namira (JIPRO: Journal of Intellectual Property, 2023)
Intellectual Property Rights are the result of an individual's thoughts which can be in the form of ideas, thoughts, or ideas by expressing them in a form of invention in works of art, literature, or in the field of science that have economic value. One of the Intellectual Property Rights is Copyright. Authors have Moral Rights and Economic Rights, so licenses and royalty payments are required for the commercial use of copyrighted works. This research has formulated the problem of how the rules regarding Copyright, especially regarding songs and/or music in Indonesia, and what legal remedies can be taken for violations of performing songs without permission. The research method in this study used descriptive-analytical research with normative juridical methods. Copyright is regulated in Law Number 28 of 2014 concerning Copyright. Commercial use of copyright works without permission will be subject to sanctions as stipulated in Article 113 paragraph (2) of Law no. 28 of 2014, namely imprisonment for a maximum of 3 (three) years and/or a maximum fine of Rp. 500,000,000.- (five hundred million rupiah).